An Appraisal of On Line Customer Services (A Case Study of SBI) - Yadav, Arvind Kumar (Journal of Commerce and Trade, 2009)
The Bank’s efforts to improve efficiency and Customer service through use of technology are related in the rapid pace of its branch computerization. In order to provide better Customer service, business hours have been extended in 1840 computerized branches in the country. With a view to helping the Customers to have access to the information regarding their accounts round-the clock, through Internet, the Bank has introduced ‘ Online State Bank of India’ from the 1st August. The Bank has appointed a firm of consultants for drawing up its IT plan. The plan covers IT architecture for the Bank and business solutions including e-commerce, Payment gateways and networking of all computerised branches.